Russian Federation : Detailed Assessment of Observance of IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2012)
This assessment reviews the regulatory framework in place for the oversight of the capital markets of the Russian Federation as of June 2011. The Russian securities markets, in particular, have been volatile, reflecting the inflow and outflow of money and the crisis. Foreign investment banks report that USD 20 billion of foreign investment exited the markets during the first quarter of 2011. This volatility is continuing, and is reflected in the changes in market capitalization in relation to GDP.